Clinical outcomes of minimally invasive ceramic restorations executed by dentists with different levels of experience. Blind and prospective clinical study - Rocha, Eduardo Passos [UNESP]; Anchieta, Rodolfo Bruniera [UNESP]; Melo, Regis Alexandre da Cunha [UNESP]; Dos Santos, Paulo Henrique [UNESP]; Assunção, Wirley Gonçalves [UNESP]; de Souza, Fernando Isquierdo [UNESP]; Martini, Ana Paula [UNESP] (Japan Prosthodontic Society, 2021)
Purpose: To evaluate the clinical outcomes of minimally invasive ceramic restorations executed by dentists with different levels of experience. Methods: Sixteen professionals were divided into 4 groups according to their experience levels. These included G1: up to 2 years since graduation, G2: 2-5 years, G3: 5-10 years, and G4: more than 10 years. All professionals were trained to follow the same standardized clinical protocol, but were unaware of the research objectives. A single evaluator followed the clinical treatments and recorded the complications and errors that occurred during the execution of the protocol. Ninety-one full crowns, 137 veneers, and 46 no-preparation veneers were prepared from lithium disilicate. Follow-ups were performed immediately and at 30, 180, and 360 days after the cementation and the evaluation based on the modified United States Public Health Service criteria. Ceramic chipping/ fracture and debonding were considered failures. Fractures were replicated and submitted to fractographic analysis. Results: The highest number of failures were found in G1 followed by G3 and the lowest number of failures were found in G2. The level of success was 94% after 360 days. The fractographic analysis demonstrated the external surface of restorations as the critical area and suggested that failures might occur due to noncompliance with the clinical protocol. There was no correlation between professional experience and number of failures or patient satisfaction. Conclusions: Professional experience was not a decisive for patient satisfaction and success of minimally invasive ceramic restorations, and noncompliance with the clinical protocol was associated with early ceramic restoration failures.
Keywords: All-ceramic; Clinical study; Dental ceramics; Minimally invasive treatment; Veneers